Pelaksanaan Supervisi Akademik Guru Pendidikan Agama Islam oleh Kepala Madrasah Aliyah Negeri di Provinsi Kepulauan Bangka Belitung - Andi Muhammad Darlis (El-Idare, 2020)
This article discusses the implementation of academic supervision by the headmaster of madrasas, supervision is assistance, guidance to teachers in the instructional field, so it is very important to hold supervision to improve the quality of teachers in teaching. This type of research is qualitative, informant madrasa head and PAI teacher. Data collection techniques are observation, interviews, documentation and data validity. The results of the study: First, the implementation of academic supervision of PAI teachers in MAN Bangka Belitung Islands Province, is MAN I Pangkalpinang not yet running optimally, MAN I Bangka Barat supervision is good, MAN1 Bangka looks supervisor is not maximal, MAN Insan Cendikia is quite good. Second, the strategy of implementing the supervision of the head of MAN 1 Bangka Belitung island province is a class visit, observation, interviews, and selecting teaching materials. The three factors supporting the completeness of learning documents, face-to-face between supervisors and teachers, motivation, and inhibiting factors of Academic supervision of PAI teachers in MAN Bangka Belitung Province are incomplete learning documents, little face-to-face between teachers and supervisors, low motivation.